The Legal of The Custodian in The Stock Market Comparative Legal Study A - Omar N. Yahya ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
After increasing in the volume of traded securities and the number of investors, especially representatives of the private sector significantly and with the implementation of privatization programs in countries, the central deposit and preservation system has been applied. The central deposit system stands on the idea of ​​converting securities from their physical form to an account or notebook entry where the ownership of these securities is transferred from one account to another.